Les sciences historiques : un impensé épistémologique dans l’enseignement de l’évolution - Fabienne Paulin; Sylvain Charlat; Éric Triquet (Recherches en Éducation)
School curricula tend to leave increasing space to epistemology in life and earth sciences, of which the evolutionary theory is a central element. In this article, we investigate how the specificities of evolutionary sciences, including both « functional » (mechanistic) and historical aspects, are taken into account in official instructions for life and earth sciences in high school. In this analysis, we assign scientific objects and approaches to either mechanistic or historical sciences, based on their distinctive features. Our results indicate that mechanistic sciences predominate in official instructions. The historical approach is virtually absent, although historical themes, that would require such an approach, are present in the curricula. We hypothesize that this paradox, resulting from an insufficiently explicit integration of historical sciences, might explain some of the repeatedly documented difficulties encountered by teachers when it comes to evolution.